2018
DOI: 10.1016/j.neuroimage.2018.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Brain network segregation and integration during an epoch-related working memory fMRI experiment

Abstract: The characterization of brain subnetwork segregation and integration has previously focused on changes that are detectable at the level of entire sessions or epochs of imaging data. In this study, we applied time-varying functional connectivity analysis together with temporal network theory to calculate point-by-point estimates in subnetwork segregation and integration during an epoch-based (2-back, 0-back, baseline) working memory fMRI experiment as well as during resting-state. This approach allowed us to fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…Second, as a result of the cross-section nature of this study, it is unclear that brain function differences we found are directly caused by Baduk training or they are pre-existing group differences that predict whether or not a person takes up Baduk rather than a result of that training. Third, considering previous studies showing an interaction between resting-state activity and stimulus-induced activity ( Northoff et al, 2010 ; Fransson et al, 2018 ) and significant differences in resting-state activity between experts and novices ( Jung et al, 2013 ; Dong et al, 2014 , 2015 ), it is speculated that different resting-state activity patterns between the two groups may be the foundation for the activity difference during task-state. Further research with both resting-state and task-stat fMRI will help to clarify this issue.…”
Section: Discussionmentioning
confidence: 95%
“…Second, as a result of the cross-section nature of this study, it is unclear that brain function differences we found are directly caused by Baduk training or they are pre-existing group differences that predict whether or not a person takes up Baduk rather than a result of that training. Third, considering previous studies showing an interaction between resting-state activity and stimulus-induced activity ( Northoff et al, 2010 ; Fransson et al, 2018 ) and significant differences in resting-state activity between experts and novices ( Jung et al, 2013 ; Dong et al, 2014 , 2015 ), it is speculated that different resting-state activity patterns between the two groups may be the foundation for the activity difference during task-state. Further research with both resting-state and task-stat fMRI will help to clarify this issue.…”
Section: Discussionmentioning
confidence: 95%
“…A novel work suggests, again, a cross-modal recruitment of sensory related short-term memory where visual memory implicated also auditory regions and, vice versa, auditory short-term memory was associated with the activity of the dorsal and ventral visual pathways (Michalka et al, 2015). Moreover, a recent work has shown fast modifications of functional connectomes and remarked the importance of even minute topological changes for the global network capacity to integrate information (Fransson et al, 2018). Eventually, our previous study focused on the alternating dynamics of segregation and integration in a visual working memory task suggested that the interchange of segregation-integration required a quasi-continuous coherent activation of most of the recorded cortical regions resulting in a global complex network orchestration (Zippo et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…Every possible state corresponds to one unique point in state-space, and the temporal evolution of the system in state-space traces a path which is called the "state-space trajectory". Here, we apply a dynamical systems perspective to assess how individual brain networks interact with each other across time, all the while the configurations of both intra-and inter-network (in this study, the DMN) connectivity are retained, which is in contrast to previously used reductionist methods of computing network segregation as one single measure averaged across the whole scan (Chan et al, 2014), or as a single time-varying measure (Fransson et al, 2018;Fukushima et al, 2018).…”
Section: Construction Of State-space Trajectories For Network Interacmentioning
confidence: 99%